2022
DOI: 10.2174/1871520621666210524164351
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Evaluation of Novel Quinazolinone Acetamides: Synthesis and Characterization

Abstract: Background: According to the global cancer report of 2019, the burden of cancer will exceed more than 18 million becoming one of the major causes of global mortality rate. There is a pressing need to establish novel drug candidates for cancer treatment, though many anticancer agents are available in the market owing to their adverse effects. In recent years, quinazoline and its derivatives have been considered as a novel class of cancer chemotherapeutic agents that show promising activity against different tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Quinazolinone and its derivatives are an essential heterocyclic skeleton that serves a prominent role in several cellular processes and have been established for their remarkable therapeutic significance as antihypertensive, antimicrobial, antihyperlipidemic, anti-inflammatory, and anticonvulsant activities ( Mhaske and Argade, 2006 ; Khan et al, 2016 ). At the same time, some of their derivatives are also used as antitumor chemotherapeutic agents ( Hekal and Abu El-Azm, 2018 ; Hakim et al, 2022 ). For instance, some representative examples of therapeutically potential quinazolinone derivatives are described in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Quinazolinone and its derivatives are an essential heterocyclic skeleton that serves a prominent role in several cellular processes and have been established for their remarkable therapeutic significance as antihypertensive, antimicrobial, antihyperlipidemic, anti-inflammatory, and anticonvulsant activities ( Mhaske and Argade, 2006 ; Khan et al, 2016 ). At the same time, some of their derivatives are also used as antitumor chemotherapeutic agents ( Hekal and Abu El-Azm, 2018 ; Hakim et al, 2022 ). For instance, some representative examples of therapeutically potential quinazolinone derivatives are described in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Because of its broad bio‐activity and structural diversity, it has become an essential functional framework for drug development [12–13] . It has anti‐tumor, anti‐tuberculosis, antibacterial and anti‐HIV‐1 activities [14–17] . It has been found that quinazolinone derivatives can inhibit the phosphorylation of EGFR and regulate the signal pathway of tumor cells, thus producing anti‐tumor cell proliferation [18] .…”
Section: Introductionmentioning
confidence: 99%